Sustainable Agro-Tourism Development through Community Based Tourism (CBT) Strategy - Iwan Zuhdi; Budi Setiawan; Dwi Retno Andriani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Agrotourism includes a reciprocal relationship between cultivated and non-biological elements that can be managed for tourism activities, so that natural characteristics determine the sustainability of the developed agrotourism. However, there are still problems in the field that raise questions about the sustainability status of agro-tourism, especially regarding four dimensions, including ecology, economy, socio-culture, and infrastructure. This study aims to analyze the variables affecting the sustainability of agrotourism in Taman Pinggir Nggawan and the sustainable development strategy of agro-tourism. The analysis method used is a quantitative analysis instrument (SEM-PLS application) and to find a development strategy, a qualitative analysis instrument (SWOT) will be used. The results show that the agro-tourism management of Taman Pinggir Nggawan towards community based sustainability (CBT) revealed a constructive and significant effect on community welfare and sustainability performance of the tourism business. This is in line with the findings observed in the field that based on the order of priority in the results of the leverage analysis, it can be seen that the change in the shape of the root mean square (RMS) of the coordinates on the X axis. Keywords: Agrotourism, Sustainability, Dimensions, Instruments, SWOT.